Avaliação da atividade gastroprotetora do ácido rosmarínico em modelos animais - Nascimento, Raphaela Francelino do (2016)
Rosmarinic acid (RA) is a secondary metabolite present in several plant species, chemically characterized as a phenolic compound, derived from the esterification of caffeic acid and 3,4-dihydroxyphenyl lactic acid. Its name is derived from Rosmarinus officinalis, a species from which it was first isolated. Several biological effects have been described for RA as the antioxidant, antiallergic, anticancer, antimicrobial, neuroprotective, hepatoprotective, among others. The objective of the present study was to evaluate the acute toxicity, the gastroprotective activity of rosmarinic acid, and related mechanisms of action in animal models. In the acute toxicity model in female mice, rosmarinic acid at doses of 300 and 2000 mg / kg, v, did not show any behavioral changes in the parameters evaluated, nor did the changes in water and feed intake, body weight and macroscopic organ structure . Due to the presence of death at the dose of 2000 mg / kg, the LD50 of rosmarinic acid was set at 2500 mg / kg, according to OECD Guideline 423, which suggested low toxicity. The gastroprotective activity of RA was evaluated at different doses of 25, 50, 100 and 200 mg / kg (v0) in different models of acute ulcer induction: acidified ethanol, ethanol, immobilization and cold stress, non-steroidal anti-inflammatory NSAIDs) and contention of gastric juice. In the pharmacological screening with acidified ethanol in mice, RA and carbenoxolone decreased the ulcerative lesion index (ILU) in 42, 42, 40, 66 and 42%, respectively, when compared to the negative control group (saline solution 0.9 %). In the ethanol model, AR (50, 100 and 200 mg / kg) and carbenoxolone (100 mg / kg) reduced the ALU by 52, 68, 96 and 93%, respectively, when compared to the negative control group. In the stress model, RA (25, 50, 100 and 200 mg / kg) and cimetdine (100 mg / kg) decreased the ILU by 39, 41, 69, 71 and 40% when compared to the saline group 0 , 9%. In the NSAID-induced ulcer model RA (25, 50, 100 and 200 mg / kg) and cimetdine (100 mg / kg) decreased the ILU by 36, 39, 49, 67 and 29% when compared to the control group negative. In the gastric juice-induced ulcer model, RA (200 mg / kg) and cimetidine (100 mg / kg) when administered orally or intraduodenal reduced ILU by 38 and 51%; 43 and 31%, respectively, when compared to their negative controls. The presence of anti-secretory or neutralizing mechanisms (biochemical parameters), cytoprotection (sulfhydryl groups, nitric oxide, muco, prostaglandin), antioxidant (GSH) and immunoregulatory (TNF-, IL-1 and IL-10) were evaluated. It was observed that the gastroprotective effect of rosmarinic acid is not related to the alteration of the biochemical parameters of the gastric juice (pH, volume and [H +]), it does not involve nitric oxide, muco and prostaglandins, but it is related to the participation of the sulfhydryl groups , increased GSH levels, reduction of proinflammatory cytokines (IL-1 and TNF-) and maintenance of anti-inflammatory cytokines (IL-10) levels. In this way, it is possible to infer that rosmarinic acid has gastroprotective activity, related to cytoprotective, antioxidant and anti-inflammatory mechanisms.